2017
DOI: 10.3390/ijerph14030305
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Frequency of E-Cigarette Use and Frequency and Intensity of Cigarette Smoking among South Korean Adolescents

Abstract: Introduction: The prevalence of adolescent electronic cigarette (e-cigarette) use has increased in most countries. This study aims to determine the relation between the frequency of e-cigarette use and the frequency and intensity of cigarette smoking. Additionally, the study evaluates the association between the reasons for e-cigarette use and the frequency of its use. Materials and Methods: Using the 2015 Korean Youth Risk Behavior Web-Based Survey, we included 6655 adolescents with an experience of e-cigaret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 32 publications
4
23
1
1
Order By: Relevance
“…Our finding that, regardless of school type, the association between tobacco use and e-cigarette use, as well as morning craving, is consistent with existing findings that e-cigarette use was associated with morning smoking urge 20 and ever tobacco use 11,20 . No longitudinal study has explored the causal relationship between tobacco and e-cigarette use 7 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our finding that, regardless of school type, the association between tobacco use and e-cigarette use, as well as morning craving, is consistent with existing findings that e-cigarette use was associated with morning smoking urge 20 and ever tobacco use 11,20 . No longitudinal study has explored the causal relationship between tobacco and e-cigarette use 7 .…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that pro-tobacco advertisements increased odds of e-cigarettes use by 1.72 times, is similar to a study that found exposure to tobacco product advertisements raised e-cigarette awareness 11 . This suggests that those who are aware of or use e-cigarettes may be more attentive to or have greater exposure to tobacco-related messages.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, young adults in Great Britain may have different reasons for vaping than older adults; evidence from the US suggests that adolescents and young adults vape primarily out of curiosity 7 or because their friends/family vape 8 . In a study of South Korean adolescents, the most common reason for vaping among infrequent users was out of curiosity, but the most common reasons given for frequent vaping were to quit smoking and being able to vape indoors 9 . Vaping to quit smoking was also associated with continued vaping among US middle and high school students 10 .…”
Section: Introductionmentioning
confidence: 99%